Adolescent Health Series: HPV infection and vaccination in sub‐Saharan Africa: 10 years of research in Tanzanian female adolescents ‐ narrative review. Issue 11 (1st September 2021) - Whitworth, Hilary; Changalucha, John; Baisley, Kathy; Watson‐Jones, Deborah
Summary: Cervical cancer is the leading cause of cancer‐related morbidity and mortality in many sub‐Saharan African (SSA) countries, including Tanzania. Most cervical cancer cases worldwide are attributable to infection of the cervix with Human Papillomavirus (HPV), a vaccine‐preventable sexually transmitted infection (STI). Over the past 10 years, we have conducted a programme of HPV research in pre‐adolescents and adolescents in Mwanza, the second‐largest city in Tanzania, which is situated in a malaria‐endemic region. In this narrative review article, we summarise the contribution of our work, alongside work of others, to improve the understanding of HPV epidemiology in SSA and development of setting‐appropriate, evidence‐based intervention strategies. We present evidence for very high prevalence and incidence of HPV infection among female SSA adolescents around the time of sexual debut, describe risk factors for HPV acquisition, and discuss associations between HPV, HIV and other STIs, which are also highly prevalent within this population. We summarise findings from early clinical trials of HPV vaccines in SSA, the first of which was an immunogenicity and safety trial conducted in Mwanza, Tanzania, and Dakar, Senegal. Within the trial, we evaluated for the first time the potential impact of malaria and helminth infection on vaccine‐induced antibody responses in Tanzanian girls. We describe research evaluating optimal HPV vaccine delivery strategies within this setting, perceived requirements for and barriers to vaccine implementation among key informants from LMIC, vaccine acceptability among girls and parents, and opportunities for co‐delivery of interventions alongside HPV vaccination to an adolescent population. Finally, we discuss country‐level barriers to vaccine uptake in LMIC, and ongoing studies in Tanzania and other SSA countries of reduced‐dose HPV vaccination schedules that may alleviate cost and logistical barriers to vaccine implementation.